2015
DOI: 10.1007/s11164-015-2245-5
|View full text |Cite
|
Sign up to set email alerts
|

meso-Aryl-substituted free-base porphyrins: formation, structure and photostability of diprotonated species

Abstract: Susceptibility to interact with trifluoroacetic acid (TFA) of selected freebase porphyrins, including a novel lipophilic 3-n-pentadecyl(phenoxy)-ethoxyphenyl-substituted porphyrin, and photostability of their diprotonated compounds was explored in benzene and N,N-dimethylformamide (DMF). Results have been discussed in terms of the commonly applied pK a -based procedure and confronted with a simple approach derived from experimentally-determined correlations reflecting the porphyrins affinity for TFA. Density f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
12
1
Order By: Relevance
“…In particular, the protonated species of the electron‐withdrawing substituents ( H 2 10 2+ , H 2 15 2+ , H 2 16 2+ ), lead to an almost fifteen times higher photostability compared to H 2 2 2+ . This observation is in contradiction to previously reported data on porphyrins, which showed that diprotonated species are more prone towards photobleaching . Through the comparison of an aerated and deaerated (argon‐purged) solution of 2 , we found that photobleaching of TATBPs is an oxidative process.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In particular, the protonated species of the electron‐withdrawing substituents ( H 2 10 2+ , H 2 15 2+ , H 2 16 2+ ), lead to an almost fifteen times higher photostability compared to H 2 2 2+ . This observation is in contradiction to previously reported data on porphyrins, which showed that diprotonated species are more prone towards photobleaching . Through the comparison of an aerated and deaerated (argon‐purged) solution of 2 , we found that photobleaching of TATBPs is an oxidative process.…”
Section: Resultscontrasting
confidence: 99%
“…For all investigated samples except for 3 and 4,protonation of the inner nitrogen atoms of the macrocycle, leads to an increased photostability.I np articular,t he protonated species of the electron-withdrawing substituents (H 2 10 2 + + , H 2 15 2 + + , H 2 16 2 + + ), lead to an almost fifteen times higher photostability comparedt oH 2 2 2 + + .T his observation is in contradictiont op reviously reportedd atao np orphyrins, which showed that diprotonated species are more prone towards photobleaching. [74] Through the comparison of an aerated and deaerated (argon-purged) solution of 2,w efound that photobleaching of TATBPs is an oxidative process. The deaerated sample exhibits a6 0% higherp hotostabilityt han the aerated solution.C omparing the photobleaching efficiency of 2 with its "smaller brother" TPP,c ompound 2 shows a1 .2-times higherp hotostability,w hilei nf orm of the dication, H 2 TPP 2 + + exhibits an almost 13-times higher photostability than H 2 2 2 + + .…”
Section: Photostabilitymentioning
confidence: 99%
“…TFA is an important versatile acid (less oxidizing than H 2 SO 4 ) used as a reagent in organic synthesis, as an ion pairing agent in HPLC or solvent for NMR spectroscopy, and calibrant in mass spectrometry. It is also extensively used in studies concerning the acidic activation of porphyrins or typical mono-phthalocyanines [26,49,50]. However, in this scope the lanthanide diphthalocyanines thus far were not sufficiently explored.…”
Section: Introductionmentioning
confidence: 99%
“…Substituents attached at the level of the peripheral porphyrin ring often caused minor structural changes without modifying the planar geometry of the porphyrin core, which instead could be affected by bulky aromatic substituents on meso or β positions and also by introducing substituents at the inner pyrrole nitrogen atom. It was documented that under acidic conditions, such as trifluoroacetic acid (TFA) [ 23 ] or methanesulfonic acid (MSA) [ 24 ] in homogeneous organic solvent solutions, the porphyrin core (H 2 Por) may undergo protonation at one or both nitrogen atoms of the pyrrole units, thus resulting in either monocationic (H 3 Por + ) or dicationic (H 4 Por 2+ ) species [ 25 , 26 , 27 ] displaying perturbed photophysical properties compared to their neutral parent compounds, including altered electronic absorption spectra, substantially lowered quantum yield of triplet-state formation, and increased Stokes-shifts in fluorescence spectra [ 12 , 13 ]. The core protonation of porphyrin contributes to an out-of-plane tilting of the individual pyrrole rings, as the four hydrogen atoms do not fit into the central cavity of the macrocycle and thus generate the so-called hyperporphyrin spectra, which are characterized by a broadened and/or split Soret band along with an intense new red-shifted absorption replacing the typical Q band situated in the visible spectral region.…”
Section: Introductionmentioning
confidence: 99%